The waiting times distribution of public hospitals using a GAMLSS approach: the case of Andalusia (Spain). - Caro Navarro, Ángela; De-Haro-García, Julia (Asociación Española de Ciencia Regional, 2024)
Patients’ waiting times are caused by the imbalance between the available supply and the existing demand in the health sector. Exceeding maximum waiting times may worsen diseases and entail additional costs to public health systems. This paper studies the theoretical probability distribution that best fits the average waiting times for non-urgent surgeries and first outpatient consultations for Spanish public hospitals in the region of Andalusia. For doing this we apply Generalized Additive Models for Location, Scale and Shape, which cover a wide range of probability distributions. We propose the final selected models as a tool to be considered by health authorities for a better management of waiting times/lists.
Keywords: Hospitales - Andalucía - Listas de espera; Model selection; Waiting lists; Waiting times; GAIC; GAMLSS